METAPHORICAL PERCEPTIONS OF TEACHERS ON THE CONCEPT OF COUNSELING SERVICE - Hasan Basri MEMDUHOĞLU (Fırat University, 2019)
The aim of this study is to show the perceptions of the pre-primary school teachers regarding the counselling service. In the survey, qualitative research method was used. The perceptions teachers have regarding the counselling service got acquired by the metaphor method. During the analysis stage of datum the content analysis method was used. 32 pre-primary school teachers who teach in the city center of Diyarbakır form the study group of the survey. The findings obtained from the survey show that the majority of the pre-primary school teachers (28) who took part in the survey have positive feelings regarding the counselling service; only two participants perceive the conselling service in the negative way. The participants who have positive perceptions about the counselling service consider the six aspects of it, helping, illuminating/improving, listening/counsellor, guiding, intervening and coordinating, significant and necessary. The participants who perceive it in the negative way, on the other hand, are of the opinion that the counselling service only deals with preparing the documents for dossiers and it will not solve the behavioral problems of the children; thus, there must be psychologists in the staff.